2018
DOI: 10.1084/jem.20160659
|View full text |Cite
|
Sign up to set email alerts
|

Development of intestinal M cells and follicle-associated epithelium is regulated by TRAF6-mediated NF-κB signaling

Abstract: TRAF6 is essential for RANK-mediated NF-κB activation and is involved in the development of several types of cells. Kanaya et al. demonstrate that RANK–TRAF6-mediated NF-κB is essential for the development of M cells and FAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 48 publications
8
74
1
5
Order By: Relevance
“…RelB is retained in the cytoplasm in its latent inactive form; upon activation, it is rapidly transported into the nucleus. This event is indispensable for the initiation of M-cell differentiation and maturation 11,14 . Immunoblot analysis revealed that, after RANKL administration, the amounts of nuclear RelB in both ileal and cecal epithelium were higher for Opg −/− mice than for WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…RelB is retained in the cytoplasm in its latent inactive form; upon activation, it is rapidly transported into the nucleus. This event is indispensable for the initiation of M-cell differentiation and maturation 11,14 . Immunoblot analysis revealed that, after RANKL administration, the amounts of nuclear RelB in both ileal and cecal epithelium were higher for Opg −/− mice than for WT mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enteroid cultures have been shown to have useful practical application in the study of the signalling pathways which modulate the differentiation and maintenance of distinct epithelial cell lineages in the murine intestine including Lgr5 + intestinal stem cells [ 6 , 61 ], tuft cells [ 20 ] and antigen-sampling M cells [ 3 , 19 , 21 , 22 ]. The 3D nature of the enteroids with a layer of epithelial cells surrounding a central, closed, lumen has also been shown to be an effective system in which to model mucosal permeability [ 62 ] and the interactions of mucosally-acquired pathogenic bacteria [ 24 ], viruses [ 25 ] and protozoa [ 26 ] with the gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF6 knockout mice are prenatal and postnatal lethal [30]. Conditional knockout models revealed essential roles for TRAF6 in a variety of immune cellular backgrounds but also in epithelial cell types [31][32][33][34], indicating how important this factor is for normal cellular homeostasis. More recently, TRAF6 was also implicated in cancer signalling, by regulating epithelial to mesenchymal transition (EMT) in colon cancer [35], DNA damage in breast cancer backgrounds [36], and involvement in autophagy responses [37].…”
Section: Discussionmentioning
confidence: 99%